Crystal structure of bis(3,5-dimethyl-1H-pyrazol-4-ammonium) tetrafluoroterephthate, 2[C5H10N3][C8F4O4] - Fujisawa Kiyoshi; Harakuni Seigo; Ageishi Keigo; Tiekink Edward R. T. (Zeitschrift für Kristallographie - New Crystal Structures)
2[C5H10N3][C8F4O4], monoclinic, P21/n (no. 14), a = 6.1490(2) Å, b = 11.0063(3) Å, c = 14.0214(3) Å, β = 94.386(5)∘, V = 946.16(5) Å3, Z = 2, Rgt(F) = 0.0371, wRref(F2) = 0.1127, T = 178 K.